Formation of Presidency in the Second Polish Republic in Comparison to a Concept of Strenghtened Presidency in the Weimar Republic and Finland Under the Constitution of 1919 - Nawracaj, Weronika (Vade Nobiscum, tom XXIII/2021: Studia nad XIX i XX wiekiem, 2021)
After gaining independence on November 11, 1918, Poland faced many challenges. The state was a creation formed of the combined territories of the Prussian, Austrian and Russian partitions, which for 123 years were subordinated to different legal systems of the partitioning states. Independent Poland quickly had to work out the foundations for its own new system. This was not facilitated by the struggle for the borders of the Polish state, economic problems, the lack of a coherent centre of power and many other factors destabilizing the situation in the state. Józef Piłsudski had a great influence on the relationship between the main organs of government on the basis of constitutional law and he also managed to combine local governments into a single authority, and thus created the germ of the Second Polish Republic. The analysis of the Polish constitutional solutions shaping the presidency at that time will be enriched with considerations on the introduction of the concept of a strong presidency in the Weimar Republic, and also in Finland under the constitution of 1919. The introduced solutions shaping the presidency against the background of Polish constitutionalism, as well as German and Finnish constitutionalism, will be analysed in terms of rationalizing the system towards a strengthened head of state. The analysis of these solutions will allow to state that the Polish legislator introduced solutions typical of the concept of a strong presidency on the basis of the August Novelisation of 1926 and the April Constitution of 1935.